SERANGGA FITOFAG YANG BERASSOSIASI PADA PERTANAMAN TEBU DI KABUPATEN BONE, SULAWESI SELATAN - Abdullah, Tamrin; Thamrin, Suleha; Sabir, Muhammad (Jurnal Agroteknos, 2011)
ABSTRACT The  research was  conducted at  the  Sugar Mill  Plantation PTPN Camming, District Libureng, Bone, and continued at the Laboratory of Plant Pests and Diseases. The purpose of this study was to determine the fitofag insects associated with sugarcane (S. officinarum L.) plants at several age levels. Research method was made using several kinds of traps namely Pitfall traps, nets, traps and direct observation of yellow adhesive. Observations were made as many as 8 times, with an interval of 3 days. The research results showed that fitofag insects that were found in sugar cane plantation were dominated by Bactrocera spp (Tepritidae; Diptera), and  the  lowest insect was Family Pyralidae (Lepidoptera). Insects which were categorized as pest in sugarcane crop were Locusta sp. (Orthoptera), Wereng (Cicadellidae; Homoptera), C. lanigera (Pseudococcidae; Homoptera), Pyralidae (Lepidoptera), Gryllidae (Orthoptera), and Curculionidae (Coleoptera). Keywords: Sacharum officinarum L., phytofag insects, diversity of population